2014
DOI: 10.4088/jcp.13m08698
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of Ketamine Response in Treatment-Resistant Major Depression

Abstract: Objective The N-methyl-D-aspartate receptor antagonist ketamine has rapid antidepressant effects in treatment-resistant major depressive disorder (MDD) and bipolar depression. Clinical predictors may identify those more likely to benefit from ketamine within clinically-heterogeneous populations. Method Treatment-resistant inpatients with DSM-IV-TR-diagnosed MDD or bipolar I/II depression currently experiencing a moderate-to-severe major depressive episode were enrolled between November 2004 and March 2013. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 38 publications
(56 reference statements)
6
91
5
Order By: Relevance
“…Prior studies have found associations between clinical and demographic factors and therapeutic response to conventional antidepressants (Perlis, 2013), however, a quantitative laboratory-based behavioral or biological predictor of treatment response has remained elusive (Kapur et al, 2012;Simon and Perlis, 2010;Trivedi, 2013). Prior research involving ketamine for unipolar or bipolar depression has suggested candidate clinical or demographic variables associated with therapeutic response, including a family history of alcoholism and a higher body mass index (BMI) (Niciu et al, 2014). Candidate baseline biological predictors of antidepressant response to ketamine previously reported include a single-nucleotide polymorphism in the gene coding for BDNF (Laje et al, 2012), as well as differential responses to emotional faces within the anterior cingulate cortex during magnetoencephalography (Salvadore et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have found associations between clinical and demographic factors and therapeutic response to conventional antidepressants (Perlis, 2013), however, a quantitative laboratory-based behavioral or biological predictor of treatment response has remained elusive (Kapur et al, 2012;Simon and Perlis, 2010;Trivedi, 2013). Prior research involving ketamine for unipolar or bipolar depression has suggested candidate clinical or demographic variables associated with therapeutic response, including a family history of alcoholism and a higher body mass index (BMI) (Niciu et al, 2014). Candidate baseline biological predictors of antidepressant response to ketamine previously reported include a single-nucleotide polymorphism in the gene coding for BDNF (Laje et al, 2012), as well as differential responses to emotional faces within the anterior cingulate cortex during magnetoencephalography (Salvadore et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This includes systematic study of enriched treatment subgroups, for example, patients with treatment-resistant depression and a family history of an alcohol use disorder [Phelps et al 2009;Niciu et al 2014b] [Clinical Trials identifier: NCT02122562] or dimensional anxious depression , to develop treatment response biomarkers and other surrogate endpoints for personalized antidepressant treatment selection.…”
Section: Resultsmentioning
confidence: 99%
“…Our group recently published a secondary data analysis of 108 patients with treatment-resistant major depression (both MDD and BDep) who received a single subanesthetic dose infusion of ketamine to study the relationship between improvements in depression/anxiety and suicidality; in this sample, improvements in suicidal thinking were partially related to improvements in neuropsychiatric symptoms, explaining up to 20% of the antisuicidal effect [Ballard et al 2014]. Interestingly, in another secondary analysis of the same sample, a lack of a lifetime history of suicide attempt predicted improved antidepressant response to ketamine at 1 week post infusion [Niciu et al 2014b]. Nevertheless, as these studies were not conducted in patients who were acutely suicidal and presenting for intervention, these studies are likely investigating chronic as opposed to acute suicidal ideation with greater potential for suicidal behaviors.…”
Section: Antisuicidal Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the psychological level this is manifest as extreme self-focus and hopelessness. It are these findings concerning glutamate-ergic excitation in MDD that might explain why GABA-ergic drugs like ketamine can act so quickly (within 24 h) to bring relief to depressed patients who are suicidal (Niciu et al, 2014). GABA-ergic drugs can help dampen the self-focus, thereby making it possible that externally introduced positive stimuli can effectively reduce negative affect.…”
Section: Rumination and The Resting State Hypothesis Of Mddmentioning
confidence: 99%